Rowan LeCompte master of stained glass - Swanson, Peter (ACC Art Books, 2022)
Rowan LeCompte (1925-2014) was a world-renowned stained-glass artist best known for his work in Washington National Cathedral that spanned an unprecedented 70 years of artistic commission. Rowan LeCompte: Master of Stained Glass celebrates LeCompte's artistic inspiration, distinctive technique, and unique perspective on a medieval decorative art, which he transformed into a fine art for modern times. The book traces his fascinating trajectory, from a determined teenager to a charming octogenarian with a clear vision of what stained glass can do within and beyond cathedral walls. More than an artist biography, this book illuminates the essence of human nature and its balance of light and darkness. Growing up in Baltimore, young Rowan LeCompte was fascinated by colour and light, collecting coloured glass fragments that his older brother - Stuart, a scientist - had discarded from his lab at Johns Hopkins. A visit to the Washington National Cathedral at age 14 would prove transformative for LeCompte, who later described the day as his second birthday. At age 15, LeCompte knew what he wanted to do for the rest of his life: combine his love of architecture and painting through the study of stained glass. Just a year later, he earned his first commission in the National Cathedral: the very place that forged his destiny. Rowan LeCompte's seven decades of work not only fulfilled his teen ambition beyond expectations - it changed the art of stained glass itself
Keywords: LeCompte, Rowan -- 1925-2014; Geschichte 1942-2014; Glasmalerei